Pengaruh Teknologi Artificial Intelligence (AI) terhadap Perkembangan Pendidikan Hukum di Indonesia - Pandri Zulfikar (Journal on Education, 2023)
This research aims to determine the influence of AI technology on the development of legal education in Indonesia. This research is a type of meta-analysis research. The data source comes from analysis of 11 national and international journals indexed by Sinta, Scopus and Web of Science. Search for sources using Google Scholar, ProQuest, ScienceDirect and Researchgate. Inclusion criteria are research originating from journals or proceedings indexed by Sinta, Scopus and WOS, research related to AI technology on legal development in Indonesia and having complete data to obtain effect size values. Data analysis with the help of the JSAP application. The research results show that the mean effect size value is (ES = 0.971), the criterion for a high effect size. These findings explain that artificial intelligence (AI) technology has a significant influence on legal developments in Indonesia.